Effects of Laser Irradiation on Pulp Cells Exposed to Bleaching Agents - Lima, Adriano F.; Basso, Fernanda G.; Ribeiro, Ana P. D.; Bagnato, Vanderlei S.; Hebling, Josimeri [UNESP]; Marchi, Giselle M.; Souza Costa, Carlos A. de [UNESP] (Wiley-Blackwell, 2014)
The aim of this study was to evaluate the effect of low-level laser therapy (LLLT) on odontoblast-like cells exposed to a bleaching agent. Mouse dental papilla cell-23 cells were seeded in wells of 24-well plates. Eight groups were established according to the exposure to the bleaching agent and LLLT (0, 4, 10 and 15Jcm(-2)). Enamel-dentin disks were adapted to artificial pulp chambers, which were individually placed in wells containing Dulbecco's modified Eagle's medium (DMEM). A bleaching agent (35% hydrogen peroxide [BA35%HP]) was applied on enamel (15min) to obtain the extracts (DMEM+BA35%HP components diffused through enamel/dentin disks). The extracts were applied (1h) to the cells, and then subjected to LLLT. Cell viability (Methyl tetrazolium assay), alkaline phosphatase (ALP) activity, as well as gene expression of ALP, fibronectin (FN) and type I collagen, were evaluated. The bleaching procedures reduced the cell viability, ALP activity and gene expression of dentin proteins. Laser irradiation did not modulate the cell response; except for FN, as LLLT decreased the gene expression of this protein by the cells exposed to the BA35%HP. It can be concluded that BA35%HP decreased the activities of odontoblasts that were not recovered by the irradiation of the damaged cells with low-level laser parameters tested.